(untitled) (Eurasian Journal of Engineering and Technology, 2023)
As the article describes, due to the increase in the number of electricity generation equipment based on renewable energy sources and consumers of electricity obtained from them it will be necessary to integrate the sources, consumers and control units that produce them and autonomous power systems efficiency power is reduced. Due to uneven production and consumption of electricity renewable energy sources under the influence of external conditions (wind, solar radiation, etc.), renewable energy sources must be backed up using conventional energy in the so-called hybrid mode, where conventional alternators must work together with renewable energy. This increases the power of electrical sources. In this case, the task of creating a tracking inverter that converts direct current into direct current, according to the characteristics of the generator, alternating current appears. O’telbayev Azizbek, a student of the Nukus Mining Institute, has been conducting experimental studies of the DC inverter. They control the conversion the reference AC network signals or the microcontroller signal are mode linked. The proposed devices are designed for full automation of energy production processes and power designed for consumption processes and input, management in hybrid power supply systems generation capacities and energy consumers to ensure maximum power efficiency production from renewable energy sources is envisaged